2019
DOI: 10.12968/bjon.2019.28.11.682
|View full text |Cite
|
Sign up to set email alerts
|

Does oral care with chlorhexidine reduce ventilator-associated pneumonia in mechanically ventilated adults?

Abstract: Oral colonisation by pathogens contributes to contracting ventilator-associated pneumonia (VAP). The aim of this review was to determine whether the use of the antiseptic chlorhexidine in the intra-oral cavity reduced its incidence in the critically ill, mechanically ventilated adult. The findings from this review led to the conclusion that chlorhexidine reduced the occurrence of VAP. Although a recommendation to implement the use of intra-oral chlorhexidine for mechanically-ventilated patients within critical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 33 publications
1
14
0
1
Order By: Relevance
“…In 2014, Zhang et al compared the effects of various concentrations of CHX and concluded that 0.12% CHX was the best option with respect to cost, adverse reactions, drug resistance, and VAP prevention [53]. However, in 2019, Jackson and Owens pointed out that, although CHX shows a clear effect in preventing VAP in ICU patients, standard guidelines, such as the usage and frequency of CHX use, have not yet been established [54]. CHX demonstrates an almost 75-90% antibacterial effect even if it is applied in the oral cavity for 15 s [55].…”
Section: Application Of Chxmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2014, Zhang et al compared the effects of various concentrations of CHX and concluded that 0.12% CHX was the best option with respect to cost, adverse reactions, drug resistance, and VAP prevention [53]. However, in 2019, Jackson and Owens pointed out that, although CHX shows a clear effect in preventing VAP in ICU patients, standard guidelines, such as the usage and frequency of CHX use, have not yet been established [54]. CHX demonstrates an almost 75-90% antibacterial effect even if it is applied in the oral cavity for 15 s [55].…”
Section: Application Of Chxmentioning
confidence: 99%
“…Many studies have shown the effectiveness of oral hygiene management, including the application of CHX, for respiratory disease prevention in ICU patients [6,11,21,41,47,48,51,53,54,56,60,61,[67][68][69][70][71][72][73][74][75][76]. In 2013, Hillier et al reported that the education of nurses on oral care, including CHX application and other oral care methods, reduced the incidence of VAP [3].…”
Section: Outcomes Of Oral Management Of Icu Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Its use for oral hygiene in patients under mechanical ventilation reduces the risk of VAP ( 16 - 19 ). As a mouthwash, CHX reduces bacterial colonization in the oral cavity ( 20 , 21 ). However, the presence of a biofilm on the surface of the teeth limits the action of any mouthwash ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is necessary to consider the negative effects that will be experienced by patients. Antibiotic resistance and risk of aspiration are some of the effects that can be fatal in patients [2], so it is necessary to find alternatives in oral care regimens.…”
Section: Introductionmentioning
confidence: 99%